2017
DOI: 10.2527/jas2017.1611
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sire family and production environment (temperate vs. tropical) on performance and thermoregulation responses in growing pigs1,2

Abstract: The aim of this study was to evaluate the effect of 2 climatic environments (temperate [TEMP] vs. tropical humid [TROP]) on production and thermoregulation traits in growing pigs. A backcross design involving Large White (LW; heat sensitive) and Creole (CR; heat tolerant) pigs was studied. The same 10 F LW × CR boars were mated with related LW sows in each environment. A total of 1,298 backcross pigs ( = 634 pigs from 11 batches for the TEMP environment and = 664 pigs from 12 batches for the TROP environment) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The effects of tropical climate on performance from 11 to 23 wk of age have already been detailed by Rosé et al (2017). In the subset of pigs with fecal samples included in our study, we confirmed that ADFI and ADG were significantly reduced in TROP compared with TEMP climate.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The effects of tropical climate on performance from 11 to 23 wk of age have already been detailed by Rosé et al (2017). In the subset of pigs with fecal samples included in our study, we confirmed that ADFI and ADG were significantly reduced in TROP compared with TEMP climate.…”
Section: Discussionsupporting
confidence: 85%
“…In TROP, the combined effects of high temperature and high relative humidity possibly accentuate the ADFI reduction due to heat (Granier et al, 1998) due to the low ability of the pigs to lose heat by evaporation under high ambient humidity. In agreement with Rosé et al (2017), feed efficiency tended to increase in TROP conditions. As suggested by Renaudeau et al (2011), in moderate HS conditions, feed efficiency increases due to feed restriction effect.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…(2017) and Rosé et al . (2017) showed that differences between temperate and tropical climates can cause significant genotype by environment interaction (G×E), which affects productivity. This breed-by-environmental mismatch is usually estimated as G×E, the genetic correlation for a given set of traits estimated in two environments.…”
Section: Discussionmentioning
confidence: 99%